Face processing in Malaysian Chinese adults - Tan, Chrystalle B. Y. (2014)
Cross-cultural studies have identified a distinct holistic-analytic pattern that observers employ in various cognitive and perceptual tasks. Recent face perception studies utilizing eye tracking methodologies have also revealed distinct Eastern and Western viewing patterns when recognizing identities and emotions. However, studies exploring genetic and cultural factors found that British born Chinese observers employed either Eastern or Western eye movement strategies, suggesting that a simple Eastern-Western distinction does not fully explain the diversity in observers’ eye movement strategies. Although Malaysia is an East Asian country, it is strongly multicultural and heavily influenced by Western culture. This thesis aimed to investigate Malaysian Chinese participants’ eye movement strategy and recognition abilities by requiring participants to perform static and dynamic face recognition, and emotion recognition tasks on African, East Asian, and Western Caucasian faces.